Psychobiological Evaluation of Day Clinic Treatment for People Living With Dementia – Feasibility and Pilot Analyses - Wuttke-Linnemann, Alexandra; Palm, Svenja; Geschke, Katharina; Skoluda, Nadine; Bischoff, Theresa; Nater, Urs M.; Endres, Kristina; Fellgiebel, Andreas (Frontiers in Aging Neuroscience, 2022)
Background: Hospitalization is often stressful and burdensome for people living with dementia (PwD) and their informal caregivers (ICs). Day clinic treatment may provide a suitable alternative, but is often precluded by a diagnosis of dementia. Furthermore, it is often caregiver-based ratings that measure treatment success as the validity of self-reports in PwD is critically discussed. We therefore set out to examine the feasibility of psychobiological stress measures in PwD and ICs and to evaluate treatment trajectories considering both the day clinic context and the daily life of the dyads. Method: A total of 40 dyads of PwD (mean age: 78.15 ± 6.80) and their ICs (mean age: 63.85 ± 13.09) completed paper-and-pencil questionnaires (covering stress, depressive symptoms and caregiver burden among others) in addition to the measurement of hair cortisol concentrations (HCC) at admission, discharge, and follow-up six months after day clinic treatment. As part of an ambulatory assessment, for two days at the beginning and two days at the end of the day clinic treatment, PwD and ICs collected six saliva samples per day for the analysis of salivary cortisol (sCort) and alpha-amylase (sAA). Results: Paper-and-pencil questionnaires and HCC assessments were more feasible than the ambulatory assessment. We found discrepancies between subjective and physiological markers of stress in PwD. Whereas HCC decreased over time, self-reported stress increased. Child-parent dyads reported decreases in neuropsychiatric symptoms, associated burden, and self-reported stress from admission to follow-up. In daily life, both PwD and ICs showed characteristic diurnal profiles of sAA and sCort, however, we found no differences in summary indicators of salivary stress markers over time. Discussion: The psychobiological evaluation was feasible and added informative value, underlining the potential of physiological stress markers to complement self-reports on stress in PwD and to objectively evaluate treatment trajectories. In this sample, HCC was more feasible and acceptable as biological marker of stress compared to saliva samples. Concerning treatment trajectories, differential effects on the dyads were found, with child-parent dyads benefitting more from day clinic treatment compared to spousal dyads.